Persistensi Laba, Dividend Payout Ratio (DPR), Mekanisme Corporate Governance (CG), Alokasi Pajak Antar Periode dan Kualitas Laba - Puspita, Indah Lia; Awan, Juni (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2021)
This study aims to provide empirical evidence of the influence of the relationship between earnings persistence, dividend payout ratio (DPR), corporate governance mechanisms (consisting of the board of directors, board of commissioners and audit committee) and the allocation of inter-period taxes on the quality of earnings in manufacturing companies listed on the Indonesian stock exchange in 2017-2019. The population in this study were 185 manufacturing companies listed on the IDX in 2017- 2019. The sample selection was done by using purposive sampling method, in order to obtain 132 research samples. The method used to analyze the data in this study is multiple linear regression with the Statistical Package for Social Sciences (SPSS) program version 21. The results of the study indicate that earnings persistence (X1) has no significant effect on earnings quality, Dividend payout ratio (X2) has a significant effect on earnings quality, The board of directors (X3) has a significant effect on earnings quality, The board of commissioners (X4) has no significant effect on earnings quality, The audit committee (X5) has no significant effect on earnings quality, Inter-period tax allocation (X6) has no significant effect on earnings quality.